Sudden cardiac death following liver transplantation: Incidence, trends and risk predictors. (15th March 2021) - Koshy, Anoop N.; Gow, Paul J.; Han, Hui-Chen; Teh, Andrew W.; Lim, Han S.; Testro, Adam; Jones, Robert; Farouque, Omar
Abstract: Background: Cardiovascular events are a leading cause of mortality following liver transplantation (LT). Although a preponderance of sudden cardiac death (SCD) in this population has been reported, there is a paucity of data evaluating the incidence, timing and predictors of SCD following LT. Methods: Using the prospectively collected Australian and New Zealand Liver Transplant Registry, a cohort study of all adult LTs from 1985 to 2017 was performed to ascertain the incidence and predictors of SCD. Recipient cause of death was adjudicated by an interdisciplinary panel. Results: 4265 LT patients were followed-up for 37, 409 person-years. SCD was the leading mode of cardiovascular death with an incidence rate of 165 per 100, 000 person-years. There was a significant increase in the hazard of SCD in the contemporary (1996–2017) vs early era (1985–1995) (hazard ratio [HR] 2.42, 95%CI 1.10–5.40; p  = 0.02). On Cox regression after adjusting for significant univariate predictors including age, coronary artery disease and non-alcoholic steatohepatitis, pre-transplant diabetes was the only independent predictor of SCD (HR 2.5 95%CI 1.1–6.0). Conclusion: SCD is the leading mode of cardiovascular cause-specific mortality following LT and diabetes was associated with a two-fold higher risk for its occurrence. Given the escalating cardiovascular risk factor profile of LT candidates, targeted therapies especially in patients with diabetes are needed to mitigate risk of post-transplant SCD. Highlights: Sudden cardiac deaths accounted for 1 in 3 cardiovascular deaths following liver transplantation Trends of sudden cardiac death over 30-years indicate a doubling in its incidence in the contemporary era Diabetes was associated with a two-fold higher risk of sudden cardiac death following liver transplantation